Healthcare costs of Type 2 diabetes in Germany. Issue 6 (9th March 2017) - Jacobs, E.; Hoyer, A.; Brinks, R.; Icks, A.; Kuß, O.; Rathmann, W.
Abstract: Aim: To describe for the first time the direct costs of Type 2 diabetes treatment by analysing nationwide routine data from statutory health insurance in Germany. Methods: This cost‐of‐illness‐study was based on a 6.8% random sample of all German people with statutory health insurance (4.3 out of 70 million people). The healthcare expenses show direct per capita costs from the payer perspective. Healthcare expenses for physicians, dentists, pharmacies, hospitals, sick benefits and other healthcare costs were considered. Per capita costs, cost ratios for people with Type 2 diabetes and without diabetes as well as diabetes‐attributable costs were calculated. Results: Per capita costs for people with Type 2 diabetes amounted to €4, 957 in 2009 and €5, 146 in 2010. People with Type 2 diabetes had 1.7‐fold higher health expenses than people without diabetes. The largest differences in health expenses were found for prescribed medication from pharmacies (cost ratio diabetes/no diabetes: 2.2) and inpatient treatment (1.8). Ten percent of the total statutory health insurance expense, in total €16.1 billion, was attributable to the medical care of people with Type 2 diabetes. Conclusions: This nationwide study indicates that one in 10 Euros of healthcare expenses is spent on people with Type 2 diabetes in Germany. In the future, national statutory health insurance data can be used to quantify time trends of costs in the healthcare system. What's new?: This is the first cost‐of‐illness study that is based on a representative 6.8% random sample of all 70 million people insured in the German statutory health insurance system. Direct per capita costs for physicians, dentists, pharmacies, hospitals, sick benefits and other healthcare expenses were calculated. Costs for sick benefits and dental care were examined for the first time. The analysis showed that one in 10 Euros of healthcare expenses is spent on people with Type 2 diabetes (€16.1 billion) in Germany. The health expenses for people with Type 2 diabetes were 1.7‐fold higher than for people without diabetes.